2016
DOI: 10.1074/jbc.m116.758516
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for β-Catenin in Modulating Levels of Insulin Secretion from β-Cells by Regulating Actin Cytoskeleton and Insulin Vesicle Localization

Abstract: The processes regulating glucose-stimulated insulin secretion (GSIS) and its modulation by incretins in pancreatic β-cells are only partly understood. Here we investigate the involvement of β-catenin in these processes. Reducing β-catenin levels using siRNA knockdown attenuated GSIS in a range of β-cell models and blocked the ability of GLP-1 agonists and the depolarizing agent KCl to potentiate this. This could be mimicked in both β-cell models and isolated islets by short-term exposure to the β-catenin inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 59 publications
7
61
1
1
Order By: Relevance
“…Hence, feeding‐induced stabilisation of β‐catenin in hypothalamic neurones may result in increased synaptic potential as a result of increased transynaptic connectivity via increased adhesion, and increased secretion by synaptic vesicle recruitment to the presynaptic membrane . We have observed a similar phenomenon in pancreatic β‐cells, where β‐catenin is stabilised in response to glucose stimulation in a cAMP/protein kinase A dependent manner, associated with increased serine 552 phosphorylation . β‐catenin stabilisation in β‐cells is important for the secretion of insulin, and knockdown via small interfering RNA transfection suppressed glucose‐dependent insulin secretion …”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Hence, feeding‐induced stabilisation of β‐catenin in hypothalamic neurones may result in increased synaptic potential as a result of increased transynaptic connectivity via increased adhesion, and increased secretion by synaptic vesicle recruitment to the presynaptic membrane . We have observed a similar phenomenon in pancreatic β‐cells, where β‐catenin is stabilised in response to glucose stimulation in a cAMP/protein kinase A dependent manner, associated with increased serine 552 phosphorylation . β‐catenin stabilisation in β‐cells is important for the secretion of insulin, and knockdown via small interfering RNA transfection suppressed glucose‐dependent insulin secretion …”
Section: Discussionmentioning
confidence: 58%
“…We have previously reported that elevations in glucose levels rapidly stabilised β‐catenin in macrophages and pancreatic β‐cells . Hence, we hypothesised that TCF/β‐catenin signalling might represent a novel glucose‐sensing mechanism in the hypothalamus.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…A study indicated that b-catenin plays a critical role in modulating insulin secretion and that the overexpression of the transcriptional co-activator of b-catenin, TCF7L2, attenuates insulin secretion [28]. The mechanism of how the overexpression of b-catenin influences insulin secretion remains unclear.…”
Section: Effector Of Wnt Signaling Pathwaymentioning
confidence: 99%